Rabbit manure compost as a peat substitute for compound growing media: Proportioning optimization according to physiochemical characteristics and seedling effects - Li, Rangling; Hao, Hongyun; Yang, Chengcai; Wang, Liangju; Wang, Hongying (Frontiers in Plant Science, 2022)
A large amount of rabbit manure is produced with the development of the rabbit industry, which will cause environmental pollution without proper treatment. Rabbit manure compost may be suitable for seedling cultivation, considering its low moisture, low heavy metal, high lignocellulose, and good fertilizer effect. In this study, a pre-proportioning test of growing media was conducted to optimize the ratio of perlite and vermiculite with peat/rabbit manure compost according to their physicochemical properties. Then, based on the results of the first proportioning optimization, the mixing ratio of rabbit manure compost and peat was further optimized using a bioassay. In this bioassay, salt-tolerant calendula (Calendula officinalis L.) and salt-intolerant cucumber (Cucumis sativus L.) were selected as test plants. The seedling effects (e.g., seedling emergence percentage, plant growth parameters, plant biomass, and nutrient effects) were evaluated. It was shown in the results that the rabbit manure compound growing media could be used for the seedlings, and suitable seedling performance was obtained with the increase of the total porosity (5.0% ~ 61.2%), organic matter content (8.3% ~ 39.9%), and nutrient elements from the rabbit manure compost. From the perspective of seedling emergence, there was no significant difference between rabbit manure compound media and peat treatment, in which the highest emergence percentages were > 90%. At the same time, the nutrient performance of plant aboveground was significantly increased in rabbit manure compound growing media compared to peat treatment. Especially, the contents of P and Mg were increased by 31% ~ 141.4% and 80.4% ~ 107.8% for calendula and by 82.6% ~ 117.4% and 35.1% ~ 67.6% for cucumber. It was indicated in the two-step optimization that the rabbit manure compost proportion of 30% ~ 50% (that is, 60% ~ 100% instead of peat) was more suitable. Additionally, the greenhouse gas emission could be reduced by using rabbit manure compost replacing peat, and the greenhouse gas emission reduction potential would be 3.65 × 10^5 ~ 4.06 × 10^8 kg CO2-equivalent/year in China, which has important ecological significance.